2019
DOI: 10.1111/hdi.12754
|View full text |Cite
|
Sign up to set email alerts
|

Brain white matter microstructure in end‐stage kidney disease, cognitive impairment, and circulatory stress

Abstract: Introduction: Structural and functional brain white matter abnormalities are poorly characterized in patients with end‐stage kidney disease. Methods: We examined the prevalence of the brain white matter microstructure disruption using diffusion tensor magnetic resonance imaging and its association with hemodynamic performance and cognitive defects in 49 incident hemodialysis (HD) patients and compared these to 25 age‐matched normal controls. We analyzed fractional anisotropy (FA) and mean diffusivity (MD) maps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 50 publications
0
29
0
1
Order By: Relevance
“…34 This may explain why HD patients develop new diffuse subcortical white matter injury that is independent of the traditional cardiovascular risk factors (smoking, diabetes, and ischemic heart disease) shortly after initiation of dialysis. 5 The mechanism of CVR impairment in HD patients is unclear. Preserved CVR in CKD patients that is independent of eGFR suggests that CVR impairment in HD patients is not simply due to reduction in renal function but is in some way related to the hemodialysis treatment.…”
Section: Cvr In Patients With Renal Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…34 This may explain why HD patients develop new diffuse subcortical white matter injury that is independent of the traditional cardiovascular risk factors (smoking, diabetes, and ischemic heart disease) shortly after initiation of dialysis. 5 The mechanism of CVR impairment in HD patients is unclear. Preserved CVR in CKD patients that is independent of eGFR suggests that CVR impairment in HD patients is not simply due to reduction in renal function but is in some way related to the hemodialysis treatment.…”
Section: Cvr In Patients With Renal Diseasementioning
confidence: 99%
“…2 Furthermore, several studies have demonstrated reduction in cerebral blood flow (CBF) during HD sessions, 3,4 which is associated with development of diffuse subcortical white matter injury and cognitive dysfunction. 3,5 Interventions that improve hemodynamic stability during HD, such as dialysate cooling, can abrogate this white matter injury, 6 potentially protecting patients from developing cognitive impairment. Although HD-associated circulatory stress represents a plausible ischemic insult, it may be superimposed on the impaired cerebrovascular function that provides an optimal milieu for ischemic injury in HD patients.…”
mentioning
confidence: 99%
“…Higher mean arterial pressure extrema points frequencies (indicative of greater hemodynamic instability) have been shown to correlate with brain white matter damage and worse neurocognitive test scores in patients on hemodialysis. 75 In a study of dialysate cooling, 73 patients on hemodialysis were randomized to dialyze with a dialysate temperature of either 37 C or 0.5 C below the core body temperature. 76 In the group randomized to a lower dialysate temperature, the mean arterial pressure extrema points frequencies and brain white matter microstructure parameters including fractional anisotropy, axial diffusivity, and radial diffusivity did not vary significantly at 12 months, indicating that dialysate cooling may be protective against chronic hemodialysis-induced brain injury.…”
Section: Dialysis and Related Interventionsmentioning
confidence: 99%
“…Tract-based spatial statistics (TBSS) and voxel-based analysis studies have found that patients with CKD have abnormal WM integrity in the corpus callosum (CC) ( Chou et al, 2013 ), fronto-temporal connections ( Drew et al, 2017 ), and anterior thalamic radiation ( Yin et al, 2018 ). However, these studies included patients with hemodialysis as subjects; long-term hemodialysis exerts gradual damage to the integrity of WM ( Kong et al, 2014 ; Drew et al, 2017 ; Eldehni et al, 2019 ), so the impact of CKD itself on WM microstructural properties remains unclear. TBSS is a method for analyzing WM fiber bundles that have been shown to improve the sensitivity of detecting WM diffusion changes, even for a relatively small sample size ( Focke et al, 2008 ; Yeh et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%